Optimal Control Strategy and Evaluation Framework for Frequency Response of Combined Wind–Storage Systems - Jie Hao; Huiping Zheng; Xueting Cheng; Yuxiang Li; Liming Bo; Juan Wei (Technologies)
The increasing integration of wind turbines into the power grid has reduced the system frequency stability, necessitating the integration of energy storage systems in primary frequency regulation. This paper proposes an MPC-based control method to optimize the frequency response of a combined wind–storage system. An evaluation system is also developed to characterize frequency response stability and guide power dispatch. First, the system model and state-space equations for MPC are established. Then, the control strategy is proposed to achieve the combined objective of minimizing power variation and frequency deviation. Finally, frequency stability is assessed using the evaluation system. MATLAB/Simulink case studies confirm the effectiveness of the proposed method in enhancing frequency regulation performance. The results show that this control strategy not only accelerates the response speed of the system frequency but also reduces its fluctuations, thereby improving the frequency stability of the system.